C60(OH)32 fullerenols: calculated temperature-sensitive isomeric interplay. Issue 12 (2nd December 2022) - Slanina, Zdeněk; Uhlík, Filip; Rodríguez-Zavala, Jaime G.; Chiang, Long Y.; Adamowicz, Ludwik
Abstract: Model quantum chemical calculations are carried out for the relative populations of two low-energy C60 (OH)32 isomers at moderate temperatures, consistently using both enthalpy and entropy components of the Gibbs energy, in order to understand the isomeric interplay at relevant synthetic conditions. The Gibbs energy is based on the M06-2X/6-311++G** energetics and M06-2X/3-21G entropy. Owing to the entropy effects, the relative populations of the C60 (OH)32 isomers change quite fast so that the equimolarity between both species is reached already at a temperature of 266 K. The calculations indicate a strong sensitivity of the C60 (OH)32 isomeric relative populations to temperature changes (a feature useful for yield optimization with a selected isomer). Calculated data on structure, charge distribution, electronic and IR vibrational spectra are presented, too. Possible roles of the inter-isomeric thermodynamic equilibrium and solubility are discussed. The results, the first of its type for polyhydroxylated fullerenes, are encouraging for further such studies with other isomeric fullerenols.